Anisotropic Supports in Metallocene‐Catalyzed Polymerizations: Templates to Obtain Polyolefin Fibers. Issue 10 (23rd April 2014) - Joe, Daejune; Golling, Florian E.; Friedemann, Kathrin; Crespy, Daniel; Klapper, Markus; Müllen, Klaus
Abstract The formation of polyethylene fibers via metallocene‐catalyzed polymerization using anisotropic organic supports as templates is presented. The supports are obtained by electrospinning a mixture of polyvinyl alcohol and functionalized polystyrene nanoparticles. After loading the MAO‐activated metallocene on the support and olefin polymerization, the obtained catalyst system yields polyethylene fibers displaying a core‐sheath structure with a controlled diameter in the range of 0.3–2 μm. This strategy represents a direct method to fabricate well‐defined polyolefin fibers and mats during the polymerization without any further processing.<inline-graphic xlink:href="ark:/27927/pgh1fd14x3j" content-type="mame201300435-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />